Intraneural Topography of Rat Sciatic Axons: Implications for Polyethylene Glycol Fusion Peripheral Nerve Repair - Hibbard, Emily A.; Sengelaub, Dale R. (Frontiers in Cellular Neuroscience, 2022)
Peripheral nerve injuries are the most common type of nerve trauma. We have been working with a novel repair technique using a plasmalemmal fusogen, polyethylene glycol (PEG), to re-fuse the membranes of severed axons. PEG-fusion repair allows for immediate re-innervation of distal targets, prevents axonal degeneration, and improves behavioral recovery. PEG-fusion of severed axons is non-specific, and we have previously reported that following injury and PEG-fusion misconnections between spinal motoneurons and their distal targets were present. Surprisingly, appropriately paired proximal and distal motor axons were observed in all PEG-fused animals. We hypothesized that a topographic organization of axons contributing to the sciatic nerve could explain the incidence of appropriate connections. We traced the course of specific axon populations contributing to the sciatic nerve in young adult male and female rats. Following intraneural injection of Fast Blue into the tibial branch, labeled axons were confined to a discrete location throughout the course of the nerve. Following intramuscular injection of cholera toxin-conjugated horseradish peroxidase into the anterior tibialis, labeled axons were confined to a smaller, but still discrete location throughout the nerve. In both cases, the relative locations of labeled axons were consistent bilaterally within animals, as well as across animals and sexes. Thus, the relatively consistent location of specific axon populations could allow for realignment of appropriate populations of axons, and enhanced behavioral recovery seen in PEG-fused animals. Knowing the organization of axons within the sciatic nerve promotes accurate territory realignment during repair, therefore aiding in recovery outcomes.